Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen Menggunakan Jasa Penginapan - Hariman Syaleh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Service quality is a way of working companies that try to hold continuous quality improvements to the processes, products and services produced by the company. This study aims to see the effect of the dimensions of service quality on customer satisfaction using lodging services at Kharisma Hotel Bukittinggi. The population of 1656 consumers and the sample in this study were 100 consumers. Data was collected through questionnaire deployment with Likert scale models then tested to the currency and reliability of the questionnaire. The data analysis technique used is the linear regression method. The results of this study are a). service quality Tangible (X1) dimension has a positive and significant influence on customer satisfaction at Kharisma Hotel Bukittinggi. b). the service quality of the Empathy (X2) dimension has a positive and significant influence on customer satisfaction at Kharisma Hotel Bukittinggi. c). the quality of service dimensions of Responsiveness (X3) there is a positive and significant influence on customer satisfaction at Kharisma Hotel Bukittinggi. d). service quality dimensions (Reliability) (X4) there is a positive and significant influence on customer satisfaction at Kharisma Hotel Bukittinggi. e) the service quality of the Assurance (X5) dimension has a positive and significant influence on customer satisfaction at Kharisma Hotel Bukittinggi. Keywords: Service Quality, Consumer Satisfaction.